Impact of cardiac rehabilitation on mortality and cardiovascular events after percutaneous coronary intervention in the community - Goel, Kashish; Lennon, Ryan J; Tilbury, R Thomas; Squires, Ray W; Thomas, Randal J (Circulation (New York, N.Y.), 2011)
Although numerous studies have reported that cardiac rehabilitation (CR) is associated with reduced mortality after myocardial infarction, less is known about its association with mortality after percutaneous coronary intervention. We performed a retrospective analysis of data from a prospectively collected registry of 2395 consecutive patients who underwent percutaneous coronary intervention in Olmsted County, Minnesota, from 1994 to 2008. The association of CR with all-cause mortality, cardiac mortality, myocardial infarction, or revascularization was assessed with 3 statistical techniques: propensity score--matched analysis (n=1438), propensity score stratification (n=2351), and regression adjustment with propensity score in a 3-month landmark analysis (n=2009). During a median follow-up of 6.3 years, 503 deaths (199 cardiac), 394 myocardial infarctions, and 755 revascularization procedures occurred in the study subjects. Participation in CR, noted in 40% (964 of 2395) of the cohort, was associated with a significant decrease in all-cause mortality by all 3 statistical techniques (hazard ratio, 0.53 to 0.55; P<0.001). A trend toward decreased cardiac mortality was also observed in CR participants; however, no effect was observed for subsequent myocardial infarction or revascularization. The association between CR participation and reduced mortality rates was similar for men and women, for older and younger patients, and for patients undergoing elective or nonelective percutaneous coronary intervention. We found that CR participation after percutaneous coronary intervention was associated with a significant reduction in mortality rates. These findings add support to published clinical practice guidelines, performance measures, and insurance coverage policies that recommend CR for patients after percutaneous coronary intervention.